Design and Development of Photography Studio Appointment Web Application - Loi, Ming Wee; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2023)
The web-based Photography Studio Appointment System is proposed and developed for Folkway Photography that currently uses manual method to handle all operations. The manual method results in great waste of time and energy, data redundancy and inconsistency, and the possibility of information being misplaced. Hence, the proposed project is intended to ease the appointment process for customers and management operation for the studio. Waterfall methodology is used in the project development, and the main languages used are HTML, CSS, and PHP. The developed system is expected to be an easy-to-use system that all users can easily access and navigate the system. Besides, the developed system is expected to reduce the workload of customers and administrator of the photography studio.